Inequalities of Schwarz–Pick type with branch points and the pseudo-hyperbolic distance. Issue 6 (3rd June 2017) - Ito, Manabu
Abstract: The classical Schwarz–Pick lemma implies that a holomorphic function of the open unit disk into itself gives a contraction with respect to the hyperbolic metric on the disk. As such, differential forms of the Schwarz–Pick lemma have been recently discussed in consideration of branch points of a holomorphic function. We in this article demonstrate that the pseudo-hyperbolic distance, which does not arise from a Riemannian metric, remains suitable for a Schwarz–Pick type of inequality even in more general settings with the existence of branch points.